Pengembangan Kompetensi Mahasiswa Melalui Pelatihan Magang Online Saat Pandemi Covid 19 - Lucky Radi Rinandiyana; Tine Badriatin; Noneng Masitoh; Andri Helmi Munawar; Rini Muflihah; Sri Sudiarti; Dede Aji Mardani; Fuzi Waliyul Mujtahidin (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
This activity is carried out in collaboration with 3 Universities in the City of Tasikmalaya with the Financial Services Institution in the Capital Market to develop student competencies through an apprenticeship training program. This activity is carried out for 30 working days starting from February 2021 to March 2021 with a rotating system considering the training period during the Covid 19 pandemic. Internships are carried out online and once a week carried out offline with a rotating system to avoid crowds and maintain health protocols. With this work apprenticeship, it is hoped that students participating in the apprenticeship who are final year students can prepare themselves in the real world of work after graduating from college, where apprenticeships are also expected to be able to apply the theories obtained during college to be able to apply them in companies or institutions where they work. This activity is carried out with assistance from lecturers and tutors from the company. The implementation of this internship resulted in participants being able to learn firsthand the stock trading system at the Indonesia Stock Exchange with direct supervision of the trading market and be able to see how the marketing administration of opening a share account.